OP88 The Hazard of Smoking for Specific Coronary Disease Phenotypes: An Electronic Health Records Study with Linked Data in 915, 000 Patients. (17th September 2012) - George, J; Herrett, E; Denaxas, S; Rapsomaniki, E; Timmis, A; Smeeth, L; Hemingway, H
Abstract : Background: The association between smoking and coronary heart disease (CHD) has been well-documented, though most studies use a composite measure of CHD. Few studies have investigated the association between smoking and specific coronary disease phenotypes, even fewer, its first manifestation. These have generally been restricted to comparison between two disease phenotypes, often with small number of events or single gender studies. Our objective is to investigate the association between smoking and initial manifestation of specific coronary phenotypes, i.e. stable angina (SA), unstable angina (UA), non ST-elevation myocardial infarction (nSTEMI), ST-elevation myocardial infarction (STEMI), and coronary death unheralded by prior symptomatic disease (UCD), within a framework of competing risks for these and other atherosclerotic diseases. Methods: This was a prospective cohort study of >915, 000 patients aged 30+ with no evidence of atherosclerotic disease in coronary, cerebrovascular or peripheral circulation prior to study entry. Using linked electronic health records from a CALIBER dataset, we incorporated primary care data from General Practice Research Data, acute coronary syndrome data from the Myocardial Ischaemia National Audit Project registry, hospital admissions data from Hospital Episode Statistics, and mortality and deprivation data from Office for National Statistics. The hazard of smoking was modelled using Cox proportional hazard regression, with data augmentation to incorporate competing risks of multiple disease presentations, and adjusted for age, sex, deprivation, blood pressure, blood-pressure lowering medication, diabetes and statin use. Results: There were 22, 815 initial coronary disease presentations and a further 48, 659 initial presentations of other cardiac, atherosclerotic cerebrovascular disease and peripheral arterial disease. Within the competing risk model, all coronary presentations showed an increased hazard for smokers compared to non-smokers, but the cause-specific adjusted hazard ratio (95% CI) for ST elevation myocardial infarction (STEMI) (2.99; 2.46–3.64) was substantially greater than those for the other presentations, including: stable angina: (1.30; 1.25–1.35), unstable angina (1.48; 1.32–1.66), non-STEMI (1.93; 1.64–2.28), and unheralded coronary death (1.58; 1.42–1.76). Conclusion: The substantial difference in the hazard of smoking between STEMI and other initial presentations suggests a specific role for smoking in the aetiology of STEMI. One limitation of this study is unrecorded risk factor data, with the potential for bias in the complete-case analysis reported here. The strengths of the study are the large cohort size with the associated large number of person years of observation and events, the clinical detail allowing typing of coronary phenotypes, the likely completeness of event capture through multiple sources of data, and the range of phenotypes compared within a single study.